2023
DOI: 10.1108/ajim-05-2022-0261
|View full text |Cite
|
Sign up to set email alerts
|

Travel vlogs influencing tourist decisions: information preferences and gender differences

Abstract: PurposeAs independent travel has become increasingly popular in recent years, factors influencing users’ attitudes and behaviors should be explored. Besides, the rise of video platforms like YouTube, Bilibili and TikTok has led to the flourishing of user generated content (UGC), among which travel vlogs have become convenient and essential references for tourists before and while they travel on their own.Design/methodology/approachThis research used quantitative analysis through a survey designed for young peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…It suggests a degree of trust and reliance on chosen sources, which in turn significantly influences how consumers interpret and react to news content. The preference for particular platforms or apps could be driven by perceived credibility, content alignment with personal beliefs, or the quality of information, all of which are crucial in shaping public opinion (Cheng et al, 2024).…”
Section: Results Of Hypothesismentioning
confidence: 99%
“…It suggests a degree of trust and reliance on chosen sources, which in turn significantly influences how consumers interpret and react to news content. The preference for particular platforms or apps could be driven by perceived credibility, content alignment with personal beliefs, or the quality of information, all of which are crucial in shaping public opinion (Cheng et al, 2024).…”
Section: Results Of Hypothesismentioning
confidence: 99%
“…, 2023), teachers need scientific arrangements and electronic device usage such as iPads. In the teaching design, students should avoid using electronic devices for other learning activities because of distraction from easily available entertainment from social media and games (Cheng et al ., 2023a, b; Wong et al. , 2023; Chan et al ., 2020).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…To cover more respondents, we plan to conduct surveys to explore the general situations for different types of schools in various regions. On the other hand, we are interested in researching the wellbeings of students (Ye and Ho, 2023) and the use of online courses and MOOCs under COVID-19 (Cheng et al ., 2023a, b; Cheng, 2022; Wang et al ., 2022c). We are also interested in using games and virtual reality to engage students in learning activities (Huang, 2023; Wu and Tu, 2023; Li and Liu, 2023; Liu et al ., 2023; Yu et al ., 2023; Zhang, 2022; Suen et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected findings are consistent with Cheung, Pires, et al (2021), where emotional engagement was not found to be a driver of consumer loyalty intention as consumers place greater importance on cognitive information especially in relation to highly involved products. As young travelers are passionate in traveling and highly involved in their trip‐planning process, they are more likely to exert greater effort in information‐search, experience sharing and social connection for group‐based travels on DBCs (Cheng et al, 2023; Jin et al, 2014). More specifically, young travelers are motivated to exert cognitive efforts to understand more about the destinations (e.g., details of events, reviews of theme parks, and opening hours of museums), and to interact with other travelers to plan their itineraries or group‐based travels via DBCs.…”
Section: Discussionmentioning
confidence: 99%